New Polypedilum Kieffer (Diptera: Chironomidae) from mountains of the Atlantic Forest, Brazil - Shimabukuro, Erika Mayumi; Trivinho-Strixino, Susana; Lamas, Carlos José Einicker (Zootaxa, 2019)
Five new species of Polypedilum from mountains of the Atlantic Forest, Southeastern Brazil, are described and illustrated as adult male. Two new species belong to the subgenus Polypedilum s. str.: Polypedilum (Polypedilum) caete sp. n. and P. (P.) aymbere sp. n. and three new species belong to the subgenus Tripodura: P. (Tripodura) yvatekaty sp. n., P. (T.) goiocoio sp. n. and P. (T.) ybytyra sp. n.